Technical Comparison of Alternatives for Voltage Sag Mitigation in Distribution Systems - Rojas, Herbert Enrique; Cruz, Audrey Soley; Rojas, Harvey David (TECCIENCIA, 2017)
In electrical systems the most critical disturbance is the interruption of the power service. However, the main concern for many commercial and industrial users is the mal-operation produced by voltage sags. This paper presents a study about the performance of a distribution system in presence of voltage sags using a distribution generation (DG) unit and a distribution static compensator (DSTATCOM). The analysis is performed by using a method for stochastic generation of disturbances and the ATP/EMTP software tool. Several case studies using the IEEE-13, bus test feeder taking to account different DG locations and penetration levels for DG unit are presented. In addition, the relation between the injected DSTATCOM reactive power, the type of sag and the location of affected nodes is considered. Simulations show that for IEEE-13 system the DSTATCOM is the best alternative for sags mitigation at a specific point in the system. However, the DG unit is an alternative that can be considered in larger distribution systems to reduce the effects of voltage sags.